STATUS UNSUR HARA KALIUM TANAH PADA LAHAN PADI SAWAH DI DESA RANTELEDA KECAMATAN PALOLO KABUPATEN SIGI - Muliadi, Muliadi; Thaha, Abd Rahim; Amelia, Rezi (Fakultas Pertanian, Universitas Tadulako, 2023)
The objective of this research was to assess the potassium nutrient status in lowland rice fields. The study was conducted in Ranteleda Village, Palolo Sub District, Sigi District, from January to June 2021. Soil samples was analyzed at the Soil Science Unit Laboratory, Faculty of Agriculture, Tadulako University, Palu. A survey method was employed in this research, and a purposive sampling technique was used to determine soil sampling locations. The soil sampling was carried out at two different depths: 0-20 cm and 20-40 cm. Each sampling point was considered as a replicate. The results revealed that soil K-Total content ranged from 38.54 to 36.62 mg/100g (moderate). The soil pH was moderately acidic, with a range of 6.23 to 5.08. The organic carbon content (C-organic) ranged from 3.31% to 2.58% (moderate). The soil CEC was found to be in the range of 13.19 to 10.54 me/100g (low). The exchangeable bases showed very low K (0.11 me/100g), very low Ca (1.16 me/100g), moderate Mg (1.15me/100g), and a moderate Na (0.31 me/100g).